Beyond the Coral Triangle: high genetic diversity and near panmixia in Singapore's populations of the broadcast spawning sea star Protoreaster nodosus. Issue 8 (August 2016) - Tay, Y. C.; Chng, M. W. P.; Sew, W. W. G.; Rheindt, F. E.; Tun, K. P. P.; Meier, R.
Abstract : The Coral Triangle is widely considered the most important centre of marine biodiversity in Asia while areas on its periphery such as the South China Sea, have received much less interest. Here, we demonstrate that a small population of the knobbly sea star Protoreaster nodosus in Singapore has similarly high levels of genetic diversity as comparable Indonesian populations from the Coral Triangle. The high genetic diversity of this population is remarkable because it is maintained despite decades of continued anthropogenic disturbance. We postulate that it is probably due to broadcast spawning which is likely to maintain high levels of population connectivity. To test this, we analysed 6140 genome-wide single nucleotide polymorphism (SNP) loci for Singapore's populations and demonstrate a pattern of near panmixia. We here document a second case of high genetic diversity and low genetic structure for a broadcast spawner in Singapore, which suggests that such species have high resilience against anthropogenic disturbances. The study demonstrates the feasibility and power of using genome-wide SNPs for connectivity studies of marine invertebrates without a sequenced genome.